Pengaruh Kompensasi Terhadap Produktivitas Karyawan Di PT. Dwipa Manunggal Kontena - Sumarsid Sumarsid (CKI ON SPOT, 2016)
This study aims to determine how the compensation effect on the productivity of employees at PT. Dwipa Manuggal  containers.  Based  on  the  analysis  of  the  correlation  coefficient  r  value  of  0.904  obtained  thereby providing  compensation showed  a  very strong  and significant  relationship  0.000>  0.05  on  the  productivity  of employees at PT. Dwipa Manuggal containers, relations between the two variables and positive direction means that any increase or decrease in compensation will be followed by an increase or decrease in the productivity of employees  at  PT.  Dwipa  Manuggal  containers.  Based  on  the  analysis  of  the  results  obtained  determinant coefficient 81.7% means that compensation has contributed greatly to the rise and fall productivity of employees at PT. Dwipa Manuggal containers, while the remaining 28.3% is influenced by factors other than compensation not I researched include: job stress, motivation and leadership styles. Calculation analysis of hypothesis testing by t test (partial) obtained results that to> t table (11.181> 1.701) These results can be concluded that to> tα. As well  as  the  significant  value  of  0000  <5%  (0.000  <0.05).  Thus  the  null  hypothesis  (Ho)  is  rejected  and  the alternative hypothesis (Ha) is accepted on a real level (level of significance) of 0.05 indicates that the hypothesis that the writer suggested that allegedly exist between the compensation effect on the productivity of employees at PT. Dwipa Manuggal containers have been proven.